Social Integration and Psychological Well-being of Elderly Women in India: A Comparative Study of Elder Women at Homes and in Elder Care Facilities - Justin Pallickal Jose and C. Shanuga (International Journal of Social Science, 2015)
In the present study, we examined the critical role of institutionalization of elder women on the social relationships, social integration and psychological well-being. A total of 194 elderly women were selected from Kannur district (Kerala) using multistage cluster sampling. Hundred and one participants were from homes and ninety three participants were from institutional care facilities. The data analyses were performed by using descriptive statistics, chi-square test for association, t’ test for independent samples and stepwise logistic regression analysis. The results revealed that the unmarried, widowed and separated elder women were more likely to be institutionalized than married elder women. Former employment, being economically active, religion and place of residence were significantly associated with institutionalization of the elder women. Objective social integration was higher among the institutionalized elderly women while subjective social integration was higher among elderly women living at homes. The elder women at homes enjoyed better family group support, better social support and more social contacts than those who were institutionalized. But the primary group concern, perceived ill health and inadequate mental mastery were higher among elder women at homes than the institutionalized. The step wise logistic regression analysis revealed that; age, marital status and perceived ill health significantly explained 58% (R 2 =0.581) of the variance on social integration. The caste affiliation and conflicts in social relationships accounted for 62.7% (R 2 =0.627) of the variance on psychological well-being. The study concluded that the socio-demographic variables, especially elder women’s residence have significant influence on social integration and psychological well- being.